(Unintended) Consequences of initiating an alcohol sales policy at college football stadiums: A case study. Issue 5 (4th July 2019) - Barry, Adam E.; Russell, Alex; Howell, Steve; Phan, Pauline; Reyes, Dominik; Bopp, Trevor
Abstract: University officials are increasingly considering selling alcoholic beverages at campus football stadiums. To inform this decision, we report on offenses occurring at a campus football stadium and surrounding community on game day weekends between 2009 and 2013. Campus police log data for 35 home football weekends were examined, accounting for 1, 940 distinct incidents. There was a general upward trend in crime incidents. On average, 330 total crime incidents occurred when alcohol was not sold (2009–2011) compared to 475 annually when alcohol was sold (2012–2013). Liquor law violations and alcohol consumption by a minor were the two most frequently cited offenses. Liquor law violations (317) was highest after alcohol sales initiated. Police incidents were markedly higher when playing a traditional football rival at home. College administrators, health officials, athletic departments, and local law enforcement must work together to weigh the potential benefit of enhanced financial profit against the risk of increased alcohol-related crime.